1 - Academic (Im)mobility: Ecology of Ethnographic Research and Knowledge Production on Africans in China - Adebayo, Kudus Oluwatoyin (Journal of Higher Education in Africa, 2022)
Since the emergence of China in the geopolitical and economic spaces of Africa, academics have followed Chinese and African people moving in both directions and conducted on-the-ground, cross-border ethnographies. However, academics are not equally mobile. This autoethnography analyses the intersections of ethnography, mobility and knowledge production on ‘Africans in China’ through a critical exploration of the contextual issues shaping the unequal participation of Africa-based researchers in the study of Africa(ns) in a non- African setting. Based on my experiences before, during and after migration to Guangzhou city, I demonstrate that ‘being there,’ fetishised as ideal-type anthropology, conceals privilege and racial and power dynamics that constrain the practice of cross-border ethnography in the global South.